Pengembangan Prototipe Sistem Peringatan Dini Tabrakan Belakang Pada Truk Berbasis Arduino - Fadli, Achmad; Supardi, Tri Wahyu (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2025)
Rear-end collisions with trucks often occur due to the lack of driver awareness in maintaining a safe following distance, as well as the presence of blind spots around the truck, especially at the rear. These blind spots make it difficult for drivers of vehicles too close to the truck to be detected, thus increasing the risk of collision, especially during sudden braking. To address this issue, this study develops a prototype of a rear-end collision early warning system based on Arduino, using TF02-Pro LiDAR and MK421137 speed sensors. This system is designed to detect the distance and speed of vehicles behind in real-time and provide an alarm warning if the distance and speed conditions reach dangerous thresholds. Testing was carried out using simulations with variations in the speed of the following vehicle at 15 km/h, 20 km/h, and 30 km/h. The results showed that the system successfully detected the speed of the following vehicle with an accuracy of 97.75% and an average error of 2.25%. Furthermore, the alarm status was successfully activated based on the predefined distance and speed thresholds. This prototype is expected to enhance road safety by providing effective early warnings to drivers behind trucks.